Data-driven Optimization Of Runway Occupancy Time Landing: A Case Study On Runway 06 at Soekarno-hatta International Airport - Wibowo, Prakoso Satrio; Sembiring, Javensius; Indriyanto, Toto (BRIN Publishing, 2025)
This study investigates how aircraft speed and altitude at threshold crossing influence Runway Occupancy Time Landing (ROTL) on Runway 06 at Soekarno–Hatta International Airport. A dataset of 2,000 ADS-B landing trajectories from Flightradar24 was analyzed to quantify empirical relationships between threshold parameters and ROTL. The 5% lowest ROTL flights showed substantially higher threshold speeds than the 5% highest ROTL flights, while threshold altitude remained nearly constant, indicating that speed is the dominant operational driver of runway occupancy. A regression-based scoring method was used to identify a representative efficient reference flight, which then served as the baseline for stochastic simulation in the BlueSky ATM Simulator. Threshold speed and altitude were sampled from normal distributions calibrated to the efficient group, and 300 simulated landings were generated. The simulation reproduced efficient operations with a mean ROTL of 51.77 s and a narrow 95% confidence interval of 51.69–51.85 s. The results support a practical recommendation to standardize threshold speed and deceleration profiles as a low-cost strategy to reduce ROTL without infrastructure modification.